European ground squirrels in backyard gardens: Identifying and mitigating agricultural conflicts with an endangered species - F. Mateos-González; L. Poledník; K. Poledníková (Animal Biodiversity and Conservation)
The European ground squirrel faces potential extinction in various countries, with populations decreasing throughout the entire range. Particularly in the Czech Republic, the mosaic landscape of private backyard gardens is now a vital habitat for the species. However, information regarding crop risks and effective, non-invasive measures for conflict mitigation are almost inexistent. To address this, we conducted field experiments examining the risk of damage for 18 common crops in backyard gardens, and tested non-invasive physical barriers to protect small plots. Our research reveals that simple fences are highly effective in safeguarding susceptible crops, particularly in areas with a high squirrel density. These findings contribute to the development of more species-specific, ecologically-based management plans and help create a sustainable future for the European ground squirrel.